2013
DOI: 10.5935/1678-9741.20130012
|View full text |Cite
|
Sign up to set email alerts
|

The use of cell saver system in cardiac surgery with cardiopulmonary bypass

Abstract: Rev Bras Cir Cardiovasc 2013;28(1):76- Abstract Introduction: The use of cell saver (CS) in cardiac surgery is proposed to reduce the use of units of packed red blood cells stored (UPRBC), which increases morbidity, mortality and causes inflammatory reactions.Objective: The objective is to evaluate whether the use of CS decreases the use UPRBC, is cost / effective and beneficial to the patient.Methods: In a prospective study, between November 2009 and October 2011, 100 consecutive patients who underwent cardio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…The study found variables that were associated with excessive bleeding after cardiac surgery with ECC in the preoperative and intraoperative periods and in the first postoperative minutes. BMI lower than 26.35kg/m 2 , ECC time longer than 90 minutes, esophageal temperature lower than 32°C, and metabolic acidosis and activated partial thromboplastin time longer than 40s were validated factors and that have already been identified in other studies 2 - 4 , 6 , 9 , 12 , 24 . On the other hand, there were variables that did not reach statistical significance values in the present study, but were considered to be associated with excessive bleeding in the abovementioned investigations.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…The study found variables that were associated with excessive bleeding after cardiac surgery with ECC in the preoperative and intraoperative periods and in the first postoperative minutes. BMI lower than 26.35kg/m 2 , ECC time longer than 90 minutes, esophageal temperature lower than 32°C, and metabolic acidosis and activated partial thromboplastin time longer than 40s were validated factors and that have already been identified in other studies 2 - 4 , 6 , 9 , 12 , 24 . On the other hand, there were variables that did not reach statistical significance values in the present study, but were considered to be associated with excessive bleeding in the abovementioned investigations.…”
Section: Discussionsupporting
confidence: 55%
“…Excessive losses tend to require corrective measures, such as transfusions, thus leading to complications, as for instance: surgical reexploration, increased mortality after 30 days, and prolongation of mechanical ventilation for more than 24 hours 1 - 3 . Hence, in recent years, there has been investment in the creation and use of more appropriate protocols to improve hemostasis 4 . The literature has presented bleeding risk factors or elements that indicate the need for transfusion in cardiac surgery, among them: the use and the discontinuation time of the use of antithrombotic agents before surgery, replacements with colloidal solutions, techniques and equipment for extracorporeal circulation (ECC), comorbidities, clinical conditions, such as coagulopathies and hemoglobinopathies and chronic diseases, such as high blood pressure, renal failure and diabetes, among other factors 4 - 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have examined the benefits of BS in cardiac surgery using cardiopulmonary bypass [ 5 , 19 ] . It has been reported that the use of BS in on-pump surgery reduces the need for transfusions compared to patients who undergo cardiac surgery without the use of BS [ 6 , 20 ] . This study showed that the duration of CPB is related to the greater use of RBC, with an average of 2.56 units of RBC in group C, 1.27 in B and 1.00 in A, however, it was not a significant factor, and the majority (n=7) from group C required RBC (2.56), 49.21% in group B and a minority (n=1) in group A.…”
Section: Discussionmentioning
confidence: 99%
“…The major aim in the use of BS is to present the ability to decrease the use of units of RBC in patients and thus reduce inflammatory reactions and mortality, with no complications or contraindication for the use of the method. This care must be taken simultaneously with a perfect hemostasis both in the initial dieresis as before synthesis in cardiovascular surgery [ 20 ] .…”
Section: Discussionmentioning
confidence: 99%
“…The use of heparin-coated circuits has also led to decreased thrombin formation [40,41], which has translated into decreased blood loss, decreased inflammation, and fewer blood transfusions [38,40]. Autologous blood transfusion eliminates some of the risks associated with homologous blood transfusion [42][43][44][45]. Although there is activation of inflammatory mediators while using a cell saver, the resultant activation is much less than with the use of a cardiotomy suction [38].…”
Section: Improvements In Cardiopulmonary Bypassmentioning
confidence: 99%